Ciri Khas Permainan Bakiak Pada Anak Usia 5-6 tahun Bengkulu Selatan - Ranny Fitria Imran; Mimpira Haryono; Runayu Runayu; Aninda Rahma Juwita; Findya Edwina; Chelsy Meizela (Early Childhood Research and Practice, 2026)
The purpose of this study was to determine whether the traditional bakiak game can improve the social–emotional development of children aged 5–6 years at PAUD Sinar Mentari, South Bengkulu Regency. This study employed Classroom Action Research (CAR), which focuses on classroom situations and is commonly known as classroom action research, using a cyclical procedure. The main subjects of this study were 15 children aged 5–6 years. The study applied the John Elliot model, in which each cycle consists of four stages: planning, implementation, observation, and reflection. The research was conducted in two cycles. Data collection techniques included observation and documentation. Data analysis was carried out using descriptive qualitative and quantitative methods. The results showed that children’s cognitive development through the implementation of the Montessori method in Group B at PAUD Sinar Mentari, South Bengkulu Regency, reached 74.16% (BSH) in Cycle I and increased to 89% (BSB) in Cycle II. The conclusion is that the traditional bakiak game can enhance the social–emotional development of children aged 5–6 years at PAUD Gemilang, Kepahiang Regency. This was evidenced by a significant improvement in Cycle II, with a percentage result of 89% (BSB).